Die Mission des American Board in Syrien im 19. Jahrhundert Implikationen eines transkulturellen Dialogs - Zeuge-Buberl, Uta (Franz Steiner Verlag, 2016)
The focus of this study is the "Syria Mission", directed by the Protestant missionary society American Board of Commissioners for Foreign Missions (ABCFM) from 1819 to 1870 in the Ottoman province of Syria, operating mainly within the territory of present-day Lebanon. The analysis of the cultural transfer between the Ottoman Empire and the United States of America undertaken in this study focuses on four relevant protagonists, whose contributions have not yet been sufficiently explored in missiological studies: The missionaries Eli Smith and Cornelius Van Dyck as well as the Syrian Protestants Butrus al-Bustani and John Wortabet. As a result, the Syria Mission of the ABCFM demonstrates how two different cultures met in a so called contact zone in the mission field and how these dialogue partners, despite many conflicts and disagreements, succeeded in contributing towards a fruitful dialogue.